Implementation of Literacy Culture in Forming Students' Integrity Character at Muhammadiyah 1 Middle School, Central Parigi - Ismartin, Ismartin; Iskandar, Iskandar; Gamar, Mahfud M. (Journal of Education Method and Learning Strategy, 2023)
As a process, education requires a programmed and stable system, as well as clear goals so that the intended direction is easily achieved. The formulation of the problem in this research is: What is the literacy culture at SMP Muhammadiyah 1 Central Parigi, How is the implementation of literacy culture in the formation of students' integrity character at SMP Muhammadiyah 1 Central Parigi, What are the supporting and inhibiting factors for the implementation of literacy culture in the formation of students' integrity character at SMP Muhammadiyah 1 Parigi Middle. The aim of the research is the supporting and inhibiting factors for the implementation of literacy culture in the formation of students' integrity character at SMP Muhammadiyah 1 Central Parigi. Literature study research method. The type of research used is literature study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials . The results of this research are aimed at collecting and reviewing various studies which conclude by looking at the results of student character and applying literacy culture in schools.